![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
展开全部
sn=n^2an
s(n-1)=(n-1)^2*a(n-1)
sn-s(n-1)=n^2an-(n-1)^2*a(n-1) =an
(n^2-1)an=(n-1)^2a(n-1)
(n+1)an=(n-1)a(n-1)
na(n-1)=(n-2)a(n-2)
(n-1)a(n-2)=(n-3)a(n-3)
……
5a4=3a3
4a3=2a2
3a2=1a1
两边相×:
3×4×5×……×(n-1)n(n+1)an=1×2×3×……×(n-3))(n-2))(n-1)a1
n(n+1)an=2a1
an=2a1/[n(n+1)]=4/[n(n+1)]。
s(n-1)=(n-1)^2*a(n-1)
sn-s(n-1)=n^2an-(n-1)^2*a(n-1) =an
(n^2-1)an=(n-1)^2a(n-1)
(n+1)an=(n-1)a(n-1)
na(n-1)=(n-2)a(n-2)
(n-1)a(n-2)=(n-3)a(n-3)
……
5a4=3a3
4a3=2a2
3a2=1a1
两边相×:
3×4×5×……×(n-1)n(n+1)an=1×2×3×……×(n-3))(n-2))(n-1)a1
n(n+1)an=2a1
an=2a1/[n(n+1)]=4/[n(n+1)]。
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询